OUT OF THE PAST: A WALK WITH LABELS AND CONCEPTS, RAIDERS OF THE LOST EVIDENCE, AND A VINDICATION OF THE ROLE OF WRITING' - Guzman Gonzalez, Trinidad (International Journal of English Studies, 2009)
'Language' and 'change' have always been inextricably united in the minds of those who have paid attention to the former, for whatever purpose, from whatever perspective and from whatever discipline. The general opinion is that language cannot be understood without change. In its turn, change cannot be explained without a proper understanding of the complex, multidimensional nature of language a task which has constantly demanded the assistance of other fields of study. Among these, sociology and recent trends in evolutionary biology have introduced new and illuminating perspectives. What I intend to do in this basically review article is (a) delimit a number of concepts and keywords which very ofien tend to be used interchangeably; (b) pose a number of questions which to my mind would deserve consideration (ofien, reconsideration), with particular referente to the role of writing as a crucial dimension of the history of, among many others, English, the language which concerns me as a researcher; and (c) frarne rny discussion within the current heoretical models which have developed from the incorporation of the above mentioned fields to historical linguistics.